Item Analysis Of Multiple Choice Questions Of Arabic Language Subjects In The Final Semester Exam - Rostianingsih; M. Baihaqi; Rustriningsih (Universitas Cokroaminoto Palopo, 2025)
Evaluation of learning outcomes is an important aspect in the educational process, especially in Arabic language learning at the Madrasah Aliyah level. The purpose of this study is to analyze the the items of multiple choice of Arabic language in the final semester exam subject grade X by reviewing five main indicators: validity, reliability, difficulty, discrimination and distraction effectiveness. The method used was descriptive quantitative with research subjects as many as 44 grade X students at MA Tasbeeh Baitul Qur'an Pinrang. The analysis showed that 80% of the questions were considered valid, and the instrument's reliability was in the high category, with an established Cronbach's Alpha value of 0.713, the difficulty level of most questions was in the medium category (50%), the discrimination of the questions was in the sufficient category (50%) with some questions still classified as poor and the distraction effectiveness found that the distractors functioned well more at 75% than the distractors functioned poorly at 25%. These findings indicate that the questions analyzed are of fairly good quality but still require revision of some items to improve the effectiveness of learning evaluation.